Cost-Effective Solution of Input Voltage Stabilizer of Auxiliary Drive Converter for Traction Vehicles - Stepanek, Jan; Jara, Martin; Drabek, Pavel (Elektronika ir Elektrotechnika, 2015)
This paper describes a prospective design concept of a hard switching input voltage stabilizer for the auxiliary drives converters of dc catenary fed light traction vehicles. Auxiliary drives are mostly dedicated to generate standard power grid that supplies various on-board equipment and charging on-board batteries. The input voltage stabilizer (IVS) is the first input block of auxiliary drives. This block defines the voltage level of the consequent dc/dc isolated converter (IC). The main aim of this paper is to present the reader with the design of a low-cost variant of the voltage stabilizer. The described input voltage stabilizer is designed as a buck (step-down) or boost (step-up) converter, operating with an input catenary voltage range of 400 (VDC) to 950 VDC. The new fast, discrete IGBT H3 transistors and SiC diodes allow switching frequency from 20 kHz to 30 kHz in a hard switching mode with power rated up to 22 kW. DOI: http://dx.doi.org/10.5755/j01.eee.21.6.13752